25.1: Invited Paper: Evaluation and standardization of light output and color gamut volume for laser projection displays. (24th February 2021) - Wang, Jianping; Hu, Qiuhong
Abstract : Laser projection displays have the advantage of light enhancement, color reproduction, luminance contrast, and dynamic range. Such projection displays are believed to produce images that look brighter and more vivid. The characterization and measurement of the displays' optical performance are important to measure the true performance of these displays. This paper introduced the evaluation of light output and color gamut volume for laser projection displays discussed in the IEC 62906‐5‐1 document.